Dependence of the diffusion wear of the hard alloy surface on its fractal dimension; IOP Conference Series: Materials Science and Engineering; Vol. 177 : Mechanical Engineering, Automation and Control Systems (MEACS 2016) - Nesterenko V. P. Vladimir Petrovich; Kondratyuk А. А. Alexey Alekseevich; Belousova E. B. Elena Borisovna; Shulepov I. A. Ivan Anisimovich (Mechanical Engineering Processes and Metals Treatment, 2017)
Title screen